2013
DOI: 10.1080/01635581.2013.767368
|View full text |Cite
|
Sign up to set email alerts
|

Crocus Sativus Stigma Extract and Its Major Constituent Crocin Possess Significant Antiproliferative Properties Against Human Prostate Cancer

Abstract: In this study, we investigated the antiproliferative effects of saffron extract (SE) and its major constituent crocin on 5 different malignant and 2 nonmalignant prostate cancer cell lines. Using high performance liquid chromatography (HPLC), the purity and content of crocin were determined. All cells were incubated with different concentrations of SE or crocin for 48 h. Cell cycle and apoptosis were also evaluated. In a time- and concentration-dependent manner, both SE and crocin reduced cell proliferation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…We observed that SE, CR, and CCT reduced tumor growth in both PC3 and 22rv1 (Figures 1 and 2) xenografts confirming our previous in vitro data [12]. In the PC3 in vivo model, the tumor mass (Figures 1(a)–1(c) and Table 1) was, respectively, reduced by 18% ( P > 0.05), 38% ( P < 0.05), and 75% ( P < 0.001) after SE, CR, and CCT treatment with respect to controls.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that SE, CR, and CCT reduced tumor growth in both PC3 and 22rv1 (Figures 1 and 2) xenografts confirming our previous in vitro data [12]. In the PC3 in vivo model, the tumor mass (Figures 1(a)–1(c) and Table 1) was, respectively, reduced by 18% ( P > 0.05), 38% ( P < 0.05), and 75% ( P < 0.001) after SE, CR, and CCT treatment with respect to controls.…”
Section: Resultssupporting
confidence: 91%
“…The bitter taste of saffron is attributed to picrocrocin, a degradation product of the zeaxanthin carotenoid and also a monoterpene glycoside precursor of safranal. Safranal is an aromatic aldehyde that is the main component of plant volatile oil [12, 13]. Studies in animal models and with cultured human malignant cell lines have demonstrated antitumor and anticancer activities of SE [11, 1419].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, increased rates of cure or remission obtained by anticancer treatments (29,30) @ C I C E d i z i o n i I n t e r n a z i o n a l i fects on numerous cancer types including those with high incidence in women of reproductive age, they may represent good candidates as protective compounds against chemo-induced gonadotoxicity (21,31). In this context, present findings represent the first evidence for the chemoprotective potential of natural antioxidant compounds against ovarian cytotoxicity and are consistent with previous results in the male gonad and other organs in mice (21,32,33). It is known that PFs are in a quiescent state by fine tuning of the PI3K/PTEN/Akt-FOXO3a pathway (17).…”
Section: Discussionmentioning
confidence: 99%
“…Results based on these findings reported that crocin reduced proliferation in all malignant cells whereas nonmalignant cells were not affected at all. 75 In addition to this, another experiment was performed to investigate the chemopreventive effect of aqueous saffron. The result of the studies reported that saffron ingestion inhibited the formation of skin papillomas and simultaneously reduced their size in animals.…”
Section: Anti-tumour Activitymentioning
confidence: 99%